2016
DOI: 10.4103/0974-2700.173867
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal injuries in communal crises: The Jos experience

Abstract: Background:Abdominal injuries contribute significantly to battlefield trauma morbidity and mortality. This study sought to determine the incidence, demographics, clinical features, spectrum, severity, management, and outcome of abdominal trauma during a civilian conflict.Materials and Methods:A prospective analysis of patients treated for abdominal trauma during the Jos civil crises between December 2010 and May 2012 at the Jos University Teaching Hospital.Results:A total of 109 victims of communal conflicts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…However, Ameh et al reported fall onto sharp objects within and around the home as the most common cause of penetrating abdominal injury in children [3]. In areas of terrorist attacks and civil war, incidence of abdominal gunshot injuries is high [17,18]. Penetrating abdominal injuries in children that occur at home usually result from accidental falls [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, Ameh et al reported fall onto sharp objects within and around the home as the most common cause of penetrating abdominal injury in children [3]. In areas of terrorist attacks and civil war, incidence of abdominal gunshot injuries is high [17,18]. Penetrating abdominal injuries in children that occur at home usually result from accidental falls [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation for the management of the remaining patients (40%) who are mostly asymptomatic with minimal or equivocal abdominal signs at the initial clinical examination is still controversial. 8,9,1…”
Section: Introductionmentioning
confidence: 99%
“…We did not perform CT scans due to the unavailability of the device during the study period. Taking into account the anatomical relationships of the abdominal cavity on the one hand, and the violence of the trauma on the other hand, extra-abdominal lesions associated with AT are very common [2][9]. Besides splenic lesions which represented 17 cases (27.42%), we recorded one case of kidney injury (1.61%) of cases in our study.…”
mentioning
confidence: 99%